Pelaksanaan Akad Jual Beli Tanah Perspektif Fiqh Muamalah - Muhammad Arsad Nasution, Era Mulyani & Syafri Gunawan & (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2020)
The problems in this thesis are how to carry out the sale and purchase of land without including the plants and how does Figh Muamalah review the land sale and purchase. The purpose of this research is to answer how the land sale and purchase is carried out. This type of research is field research, namely research that aims to obtain information and describe events and events that occur in the field according to the facts found. Using interview techniques to obtain information or data from the field. Meanwhile, the research approach used a qualitative approach with descriptive analysis. Based on the discussion in this study, the results of the research are, the implementation of the sale and purchase of land, the seller makes a sale and purchase of land which contains elements of obscurity and is not in accordance with what is received by the buyer resulting in losses to the land buyer, while if viewed from Fiqh Muamalah said the contract must be agreed beforehand that before the contract was started, the research results found in the sale and purchase of the land were not in accordance with the Fiqh of Muamalah.